The Practical Issues of Corporate Governance in China and Shareholder Meeting Centrism - Wang, Qingshe (International Journal of Social Sciences and Public Administration, 2025)
In the face of the problem of the disconnection between China’s corporate legal norms and their practical operations, there is a need to have a correct understanding of the continuous improvement of China’s shareholder investment environment, the highly concentrated shareholding structure, and the rationality of major shareholders’ active participation in company operation and management. On this basis, China should establish and improve the centrism of shareholders’ meeting in China’s corporate governance through legislation. Due to the highly concentrated equity structure in China, especially the negative impact of family authority, family interests and traditional culture of family-type companies, the control of Chinese companies is exceptionally strong; China’s legislation should clarify the legal responsibility of actual controllers and major shareholders to participate in the operation and management of the company, and establish effective internal supervision institutions, and other means to regulate the control of the company under the centrism of the shareholders’ meeting, and promote the rule of law process of China’s corporate governance.